The effect of number of blades on the horizontal axis water turbine performance - Yulio, Noviando; Herawan, Safarudin Gazali; Oktarina, Rienna; Setyandito, Oki; Mat Tokit, Ernie; Mohd Sa'at, Fatimah Al-Zahrah; Mohd Rosli, Mohamad Afzanizam (2023)
Electrical energy is energy the main essential needed in living life for various aspects of utilities related to electronics with the provisions of the need for electric power consumption in units of Watts (W). The consumption for electrical energy is increasing along with the increasing population in this country. In 2020 the installed capacity of power plants in Indonesia will reach 72,750.72 MW consisting of 43,186.53 MW from National Power Plant (PLN) and 29,564.19 MW from non-PLN. Whereas in 2019 it was only 69,678.85 MW. This data shows that the installed capacity of power plants has increased by 3,071.87 MW. Therefore, this research aims to develop the horizontal axis water turbine and to investigate the performance of turbine with varying the number of blades. The experimental rig was built to conduct the experimental work. It is found that the most optimal number of blades is the number of blades 10 which produces a value of 0.704 Watt and speed of 789 RPM using a water discharge of 11.75 Liter per Minutes (LPM), 0.855 Watt and speed of 883 RPM using a water discharge of 13.22 LPM, and 0.889 Watt and speed of 913 RPM using a water discharge of 15.17 LPM. Electrical efficiency tends to decrease when the number of blades on turbine is increased due to a significant increase in speed of turbine with increasing of blade number while the electrical energy produced by the generator is relatively constant with increasing the blade number of turbine.